Uso de wetland construído no tratamento de efluente de ranicultura - Borges, Fernanda de Freitas [UNESP] (2014)
The aim of the work was to evaluate the performance of the constructed wetland in frog culture sector for the effluent treatment in two phases of bullfrog culture. Limnological variables and the removal efficiency of nutrients were analyzed, the nutrients retention in the sediment and macrophytes used (Typha domingensis, Cyperus giganteus e Eichhornia crassipes) as well as biomass gain of the same. The treatment was efficient in a nitrate, nitrite, turbidity, total phosphorus, total suspended solids, biochemical oxygen demand, thermotolerant coliforms total, total dissolved solids and chlorophyll a. The high nutrients loads found in the phase of the high biomass frog storage, with lower phosphorus removals. The macrophytes used presented biomass gain satisfactory, with nutrient concentrations above the sediment. The three species stocked more nutrients during the phase of the high biomass frog storage, which high nutrients load. Eichhornia crassipes was the specie that most stored nitrogen and phosphorus in both phases and greater biomass gain in the phase of the high biomass frog storage. From the emerged species, T. domingensis showed the higher biomass gain in both phases, stocking all nutrients in the phase of the high biomass frog storage. There was a tendency of reduction of the organic matter in the sediment in both phases of the inlet to the outlet of wetland due to the presence of macrophytes. This same pattern of reduction was observed relation to the sediment. It was concluded that the treatment system implanted was efficient in improving the quality of the effluent, reducing nutrient and fecal coliform. The macrophytes played an important role in the reduction of such components and may be used to treat effluents of the frog culture